Association between the oxidative balance score and diabetic kidney disease in diabetes mellitus patients: insights from NHANES 2011–2018 - Li, Qiuhong; Wang, Liuwei; Yang, Zijun; Wang, Yulin; Yu, Lu; Guo, Yanhong; Zhai, Zihan; Liang, Yan; Song, Dongxu; Tang, Lin (Frontiers in Nutrition, 2026)
BackgroundOxidative stress plays a crucial role in the onset and progression of diabetic kidney disease (DKD). The oxidative balance score (OBS) evaluates an individual’s dietary and lifestyle exposures related to oxidative stress. However, the association between the OBS and DKD remains unclear. This study aimed to investigate this association in patients with diabetes mellitus (DM).MethodsThis cross-sectional study included 1,882 participants, representing 19.5 million individuals with DM, from the National Health and Nutrition Examination Survey (NHANES) collected between 2011 and 2018. The OBS was calculated using 20 dietary and lifestyle factors. DKD was defined as impaired glomerular filtration rate (estimated glomerular filtration rate [eGFR] < 60 mL/min/1.73 m2), albuminuria (urinary albumin-to-creatinine ratio [ACR] ≥ 30 mg/g), or both in DM patients. The association between the OBS and DKD was examined using weighted logistic regression and subgroup analyses.ResultsThe OBS was negatively associated with DKD. The multivariable-adjusted odds ratio (OR) for DKD per unit increase in the OBS as a continuous variable was 0.92 (95%CI: 0.85–0.99). When analyzed as a categorical variable, participants in the highest OBS quartile had significantly lower odds of DKD (OR: 0.26, 95%CI: 0.07–0.98) than those in the lowest quartile (p < 0.05). Further analyses revealed that the dietary OBS, but not lifestyle OBS, was significantly associated with DKD. The OBS had significant correlations with DKD among male patients. Among dietary components, fiber, carotene, niacin, vitamin C, calcium, and magnesium were the most strongly associated with lower odds of DKD.ConclusionOur findings revealed a significant negative association between OBS levels and the presence of DKD in DM patients, suggesting that a higher antioxidant-rich diet score is associated with a lower likelihood of DKD. Future prospective studies are needed to confirm whether adopting such a lifestyle could serve as a strategy for DKD prevention.